Swimming Facilities Management System for Universiti Tun Hussien Onn Malaysia Sport Centre with Two-Factor Authentication - Shahrom, Danial; Mohamad Sukri, Kharul Amin (Applied Information Technology And Computer Science, 2025)
The Swimming Facilities Management System for Universiti Tun Hussein Onn Malaysia (UTHM) Sports Centre with Two-Factor Authentication was developed to address inefficiencies in the management of swimming pool facilities and improve the overall operations of the Sports Centre. The existing manual process such as an inefficient booking process for swimming pool activities, a poor data management for users and an inefficient payment process for walk-in users, have proven to be time-consuming and prone to errors. To resolve these issues, the project adopts the Waterfall methodology, which provides a structured, sequential approach with a focus on clear documentation and well-defined requirements at each stage of development. The project aims to design a proposed system by implementing Role-Based Access Control, developing secure management system with Two-Factor Authentication and testing the functionality of the developed system. The expected outcome is a userfriendly interface that allows students, staff, and visitors to efficiently manage bookings, process payments, and access services, while securely handling user data.